2019
DOI: 10.1021/acs.jproteome.9b00657
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Variable Glycosylation in Nontypeable Haemophilus influenzae

Abstract: Non-typeable Haemophilus influenzae (NTHi) is a leading cause of respiratory tract infections worldwide and continues to be a global health burden. Adhesion and colonisation of host cells are crucial steps in bacterial pathogenesis, and in many strains of NTHi interaction with the host is mediated by the high molecular weight adhesins HMW1A and HMW2A. These adhesins are N-glycoproteins which are modified by cytoplasmic glycosyltransferases HMW1C and HMW2C. Phase variation in the number of short sequence repeat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 82 publications
3
14
0
Order By: Relevance
“…Our results suggest that glycoprotein production systems based on NGT expression in E. coli may suffer from the low UDP-Glc levels (typically, 1-2 mM), 56 as that may lead to premature product inhibition. In agreement with other reports, 31 we found that the glycosylation of HMW1ct is highly dependent on the levels of NGTs. This may limit the usefulness of future vaccines against glycosylated HMW adhesins, as bacteria may express different NGT levels under changing conditions, resulting in differently glycosylated adhesins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggest that glycoprotein production systems based on NGT expression in E. coli may suffer from the low UDP-Glc levels (typically, 1-2 mM), 56 as that may lead to premature product inhibition. In agreement with other reports, 31 we found that the glycosylation of HMW1ct is highly dependent on the levels of NGTs. This may limit the usefulness of future vaccines against glycosylated HMW adhesins, as bacteria may express different NGT levels under changing conditions, resulting in differently glycosylated adhesins.…”
Section: Discussionsupporting
confidence: 93%
“…This effect has been observed before in an ex vivo expression system of HiNGT and HMW1A (full-length H. influenzae adhesin), where the increasing expression of HMW1A resulted in a reduction of site-specific glycan occupancy. 31 We performed overnight glycosylation reactions in which the ratio ApNGT:HMW1ct was kept constant at 1:100, and the ratio of HiNGT:HMW1ct at 1:10, while the concentration of HMW1ct was varied from 5 μM to 100 μM ( Figure S9), and the UDP-Glc concentration was fixed at 1 mM. Indeed, upon increasing the concentration of HMW1ct in the ApNGT-catalyzed reaction, the final distribution of glycoforms reduced from 7-Glc to 9-Glc (5 μM HMW1ct) to 1-Glc to 5-Glc (100 μM HMW1ct).…”
Section: Glycosylation Of Hmw1ct Proceeds Via An Initial Fast Processmentioning
confidence: 99%
“…SSR tracts located in the open reading frame of a gene can result in the gene being in frame and expressed (ON) or, due to a frameshift downstream of the SSR tract, out of frame and not expressed (OFF). SSR tracts also occur in the promoter of a number of genes ( 9 11 ), and variation in length of these SSRs can lead to ON-OFF switching of gene expression or result in a gradient of high- to low-level expression dependent on the length of the SSR tract ( 12 ). Several bacterial pathogens also contain well-characterized cytoplasmic N 6 -adenine DNA methyltransferases, which are part of restriction-modification (R-M) systems, that exhibit phase-variable expression.…”
Section: Introductionmentioning
confidence: 99%
“…Phase variation is the rapid and reversible switching of gene expression, and it plays an important role in the pathogenesis of many organisms, where it is usually associated with expression of surface factors such as capsules (5) and adhesins (6,7) and with lipooligosaccharide biosynthesis (8). Randomized gene expression as a result of phase variation can complicate vaccine development, as it results in an unstable antigenic repertoire, and is potentially a major cause of vaccine escape.…”
mentioning
confidence: 99%